EVALUATION OF TIME-WEIGHTED CUMULATIVE HEAD IMPACT EXPOSURE METRICS ON DIFFUSION-BASED IMAGING METRICS IN YOUTH FOOTBALL - Puvvada, Suraj (Wake Forest University, 2021)
Head impacts sustained in football represent one of the largest sources of head injury and subconcussive head impact exposure (HIE) in the United States, and their effects on the brain can be devastating in the short and long term. Current efforts to understand the effects of HIE on the brain include the development of cumulative HIE metrics to assess an athlete’s exposure to head impacts over a season. Existing metrics incorporate the volume (i.e., number) and magnitude (i.e., severity) of impacts experienced by an athlete, and have been shown to be associated with structural changes in the brain observed after a single season. Another variable which has been less commonly considered is time. Incorporating time of impacts in relation to other relevant events into cumulative HIE metrics may lead to improved understanding of the effects of repeated subconcussive HIE on the brain. In the first part of this thesis, metrics of cumulative HIE that consider the volume, magnitude, and timing of impacts are evaluated with respect to total changes in diffusion-based MRI metrics. In the second part, the relationship between time-weighted cumulative HIE metrics and directional changes in diffusion-based MRI metrics is evaluated. The overall goal of this research is to evaluate the value in using time-weighted cumulative HIE metrics to understand the effects subconcussive HIE on changes in the brain after a single season.
Keywords: Brain; Diffusion Tensor Imaging; Football; Head; Magnetic Resonance Imaging; Youth Sports